Methodology of Ranking Higher Education Systems of Universitas 21 (U21) and Lessons for South East Asia Countries - Thi Quynh Lan, Mai (VNU Journal of Science: Education Research; Vol 37 No 2DO - 10.25073/2588-1159/vnuer.4501, 2021)
The quality of higher education is only assessed through “experience”, that is, through participating in the learning process. As a result, universities increasingly have to provide enough information for prospective students to choose from. The rankings were born to meet this requirement of learners and universities. International university rankings look primarily at indicators that reflect the results of scientific and teaching achievement and often ignore activities aimed at developing local communities. U21's method of ranking the world higher education systems has covered these indicators in its methodology. The four modules of U21 include: Resources, Environment, Connectivity and Outputs. Out of all 4 U21 ranking modules, Environment is the module that South East Asia countries have the best rankings. In the rankings of modules, normalization by GDP significantly reduces the scores and rankings of countries with high GDP, but increases the rankings of countries with low GDP. U21 also observed the pattern of connection between higher education institutions and enterprises. For the ASEAN countries, the transfer of common knowledge is more important than linking with business in the form of share scientific publications. Most of the countries in the U21 ranking are rich and research-oriented. The author has analyzed the U21 ranking results of 2017, 2018, 2019, 2020 of Singapore, Thailand, Malaysia, Indonesia, and drawn lessons learned for countries in South East Asia.